Orbital Shadowing for -Generic Volume-Preserving Diffeomorphisms - Manseob Lee (Abstract and Applied Analysis)
We show that -generically, if a volume-preserving diffeomorphism has the orbital shadowing property, then the diffeomorphism is Anosov.